Hands-on robotic microsurgery: robotic-assisted free flap reconstruction of the upper extremity - Strübing, Felix; Bigdeli, Amir Khosrow; Böcker, Arne Hendrik; Weigel, Jonathan; Kneser, Ulrich; Gazyakan, Emre (Journal of Clinical Medicine, 2024)
Background/Objectives: Robot-assisted microsurgery (RAMS) has been introduced into the field of plastic surgery in recent years. It potentially offers enhanced precision and control compared to traditional methods, which is crucial for complex microvascular tasks in free flap reconstructions. We aim to analyze our experiences with robotic-assisted microsurgery in the field of upper extremity free flap reconstruction. Methods: This prospective study evaluated the efficacy and safety of the Symani Surgical System for free flap reconstructions in 16 patients with upper extremity defects at our institution from February 2023 to March 2024. Operating times were compared to a matched, historical cohort. We collected data on surgical outcomes, operative times, and complication rates, following strict adherence to the Declaration of Helsinki. Results: Our cohort primarily involved male patients (81%) with defects mostly located on the hand (81%). The anterolateral thigh flap was the most commonly used free flap (14/16, 88%). The average operative time was 368 ± 89 min (range: 216-550 min). No complete or partial flap losses were observed, but one flap required revision surgery due to arterial thrombosis. Major complications occurred in 13% of the cases. The average anastomosis time was 31 ± 12 min (range: 20-35 min) for arterial end-to-end anastomoses and 33 ± 13 min (range: 20-60 min) for arterial end-to-side anastomoses. Venous anastomoses required, on average, 20 ± 6 min. Operating times were not significantly longer when compared to the historical cohort (p = 0.67). Conclusions: We were able to show comparable outcomes to conventional microsurgery, while requiring more time for the microsurgical anastomoses. The study highlights the need for larger, controlled trials to better understand the benefits and limitations of robotic assistance in microsurgical reconstruction of the upper extremity.
Gesehen am 04.03.2025